Maudu', A Union with God - Adlin Sila, Muhammad (ANU Press, 2015)
This volume offers a fascinating case study of the Sayyid community of Cikoang in South Sulawesi - in particular, an examination of the role of the descendants of Sayyid Jalaluddin al-'Aidid, a Hadhrami merchant-teacher of great authority and charisma who is said to have initially settled in Gowa in the 17th century. It is of particular interest because the migration of Sayydid Jalaluddin occurred well before the major Hadhrami diaspora to Southeast Asia in the mid-19th century. Of particular interest is the way Sayyid Jalaluddin and his descendants became integrated within the Makassar community. Sayyid Jalaluddin's legacy to the Cikoang community is the Tarekat Bahr ul-Nur, whose mystic teachings expound the creation of the world from the 'Nur Muhammad'. A consequence of this teaching is an enormous emphasis on the celebration of Maudu' (Maulid or the Birth of the Prophet) as expressed in the local assertion: 'My existence on this earth is for nothing but Maudu'.' Every year this prompts the Cikoang community to hold one of the most elaborate and colourful Maulid celebrations in Indonesia. This study was originally submitted as an MA thesis at ANU in 1998, but soon became recognised as an important contribution to Hadhrami studies. Its author, M. Adlin Sila, has since gone on to complete his PhD at ANU, Being Muslim in Bima of Sumbawa, Indonesia: Practice, Politics and Cultural Diversity. This study of Bima and its religious history establishes him as a major researcher on the diverse traditions of Islam in eastern Indonesia.